ENHANCING RECOVERY IN COMPLEX CLASTIC RESERVOIRS THROUGH DYNAMIC MODEL UPDATES AND PROACTIVE WELL MANAGEMENT - Murodov Sadriddin Nizomiddinovich (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article presents a practical, data-driven approach to improving oil recovery from mature, heterogeneous clastic reservoirs. The focus is on the operational use of surveillance data (production logs, tracers, pressure measurements) and updated sedimentological concepts to continuously refine the reservoir understanding. It details how revised parameters, such as sand body connectivity and permeability contrasts, directly influence the mapping of remaining oil saturation (ROS). Based on updated dynamic models, practical recommendations are formulated for conformance control in waterflood projects and the targeted placement of infill wells. The paper demonstrates that a systematic model-update practice can significantly improve project economics through increased well success rates and reduced water handling costs, without the need for massive capital investment.